Detection and analysis of Galileo signal in space anomalies from 2017 to 2018. Issue 11 (18th September 2020) - Fan, Lihong; Tu, Rui; Zhang, Rui; Han, Junqiang; Zhang, Pengfei; Hong, Ju; Lu, Xiaochun
Abstract : The state of the signal in space (SIS) broadcasted by the broadcast ephemeris will affect the reliability and safety of the user navigation and positioning. Understanding the SIS anomaly of a satellite is conducive to fault allocation in advanced receiver autonomous integrity monitoring. In this study, precise ephemeris was used to calculate the SIS error of all healthy Galileo satellites from 2017 to 2018, the detection thresholds were obtained through statistics of SIS error, and the satellite SIS anomalies for two years were detected. Results show that the SIS anomalies of Galileo satellites are primarily caused by satellite clock error, the scale of which can sometimes reach tens or even hundreds of metres. Except for E24 satellite, the annual accumulation of anomalies for Galileo satellites was <∼7 h, and the average annual accumulation of anomalies is ∼2.5 h. The accumulation of anomalies for E24 in 2017 was ∼50 h∼50 h, but this decreased to 4.5 h in 2018, indicating that its stability improved. Overall, the SIS stability in 2018 was improved compared with 2017. In addition, as the serious missing of broadcast ephemeris of Galileo satellites, it is not conducive to the continuity and reliability of the user's navigation and positioning.